Pleiotropic Effects of Mutations Involved in the Regulation of Escherichia coli K-12 Alkaline Phosphatase - Morris, Howard (1974)
Induction of alkaline phosphatase in wild-type Escherichia coli K-12 leads to the appearance of three new proteins in addition to alkaline phosphatase in the periplasmic space of the bacteria. These proteins are detected in autoradiograms of sodium dodecyl sulfate-acrylamide gel electropherograms of extracts from cells labeled with [(35)S]methionine. Studies with constitutive mutants defective in the three genes phoS, phoT, and phoR that have been shown to regulate alkaline phosphatase synthesis indicate that the three periplasmic proteins are coregulated with alkaline phosphatase. A mutant that has a deletion in the alkaline phosphatase structural gene phoA produces the three proteins, but a newly discovered mutant phoB that has a defect in the expression of alkaline phosphatase fails to produce the three proteins. phoB mutants are shown here to be unable to make detectable amounts of alkaline phosphatase polypeptides, as measured by immunoprecipitins or acrylamide gel electropherograms. On the basis of these results we suggest a new model for the regulation of alkaline phosphatase biosynthesis. In this model, a ternary complex composed of phoB(+) and phoR(+) gene products and an internal metabolite functions as a positive control element to regulate the transcription of several cistrons coding for periplasmic proteins.